The effect of Herbal Medicines and Supplements on Mastalgia: A systematic review and meta-analysis of clinical trials in Iran - Sedigheh Sheidaei; Morvarid Irani; Masoumeh Ghazanfarpour (Mashhad University of Medical Sciences, 2019)
Introduction: Mastalgia is one of the most common causes of women referring to treatment centers that regarding its importance, proper administration of the drug is important. Due to the complications of chemical drugs, the patients' tendency to use complementary medicine has been increased. This systematic review and meta-analysis was conducted with aim to evaluate and summarize the results of clinical trials on the effects of herbal medicines and dietary supplements on mastalgia in Iran. Methods: This systematic review and meta-analysis evaluated the effect of herbal medicines and supplements on Mastalgia by searching the articles using the keywords of mastalgia, complementary medicine, herbal medicine, their English in Persian and English journals indexed in SID, Iranmedx,  Irandoc, Magiran, Scopus,  Pubmed  and Google scholar from 2007 until 2019. The Jadad scale was used to evaluate the quality of the articles. The inclusion criteria were: the randomized controlled trials (RCTs) on mastalgia and exclusion criteria were: no access to the full text and the existence of more than one intervention in each group and lack of control group. Results: In this study, 14 articles with inclusion criteria were evaluated which had antioxidant, flavonoid, anti-inflammatory and analgesic properties and had a good effect on mastalgia relief. The obtained data supports the use of Vitagnus and vitamin E for the treatment of mastalgia. In addition, cotton seed also provided good results. The results of the meta-analysis on three studies showed no significant difference between vitamin E and Evening Primrose (p = 0.648). Conclusion: Among all the above mentioned methods, Vitagnus and Vitamin E have more evidence for use in the treatment of mastalgia. Further studies are needed to apply other methods.